THE CONCEPT OF MEDIA AND ITS ROLE IN FORMULATING STRATEGY - Alaa Adhab Briah; Asaad Dhahi Yaseen (American Journals Publishing, 2025)
between individuals, as the need for it led to it going through multiple stages of continuous development. This development has contributed to enabling individuals to coordinate and organize their activities and work through the exchange of information and ideas, which constitutes the essence of the communication process. Communication is the tool through which ideas and information are transmitted between individuals within a specific social system, which differs in its size and the nature of the relationships it includes. This system may be a mere bilateral relationship between two individuals, a small group, a local community, or even the entire human community.